Factors influencing a primary school teacher's delivery of athletics. Issue 6 (18th August 2022) - Powers, Daniel; O'Leary, Nick; Parkes, Craig
ABSTRACT: Addressing the future recommendations of the first United Kingdom primary school-based Physical Education occupational socialisation study, this case study examined how a female primary school teacher delivered athletics and those factors influencing such pedagogical practices. Data were collected from interviews and lesson observations, analysed using a thematic inductive approach and constant comparison. An 'educative' sporting perspective focusing on improving practical performance with a limited attempt to improve non-practical learning was evident alongside an emphasis on ensuring appropriate pupil behaviour. Factors influencing these practices were an influential work colleague, challenging class behaviour and enforcement of school behaviour policy. Recognising the powerful influence of the workplace on the participant's practice, school policies could encourage primary school teachers to consider attending external courses, read relevant resources, attend behavioural management courses and informally learn amongst colleagues. Future research could explore primary teachers' delivery of other activities like dance and gymnastics.